Biocontrol of ochratoxigenic moulds (Aspergillus ochraceus and Penicillium nordicum) by Debaryomyces hansenii and Saccharomycopsis fibuligera during speck production. (April 2017) - Iacumin, Lucilla; Manzano, Marisa; Andyanto, Debbie; Comi, Giuseppe
Abstract: Speck is a meat product obtained from the deboned leg of pork that is salted, smoked and seasoned for four to six months. During speck seasoning, Eurotium rubrum and Penicillium solitum grow on the surface and collaborate with other moulds and tissue enzymes to produce the typical aroma. Both of these strains usually predominate over other moulds. However, moulds producing ochratoxins, such as Aspergillus ochraceus and Penicillium nordicum, can also co-grow on speck and produce ochratoxin A (OTA). Consequently, speck could represent a potential health risk for consumers. Because A. ochraceus and P. nordicum could represent a problem for artisanal speck production, the aim of this study was to inhibit these mould strains using Debaryomyces hansenii and Saccharomycopsis fibuligera . Six D. hansenii and six S. fibuligera strains were tested in vitro to inhibit A. ochraceus and P. nordicum . The D. hansenii DIAL 1 and S. fibuligera DIAL 3 strains demonstrated the highest inhibitory activity and were selected for in vivo tests. The strains were co-inoculated on fresh meat cuts for speck production with both of the OTA-producing moulds prior to drying and seasoning. At the end of seasoning (six months), OTA was not detected in the speck treated with both yeast strains. Because the yeasts did not adversely affect the speck odour or flavour, the strains are proposed as starters for the inhibition of ochratoxigenic moulds. Highlights: The protective cultures could be employed to reduce or eliminate OTA producing moulds growth in speck. Improve the safety of speck. The bio-protective cultures influenced the microbiological but not sensorial characteristics of the speck. Debaryomyces hansenii and Saccharomycopsis fibuligera were inhibited by Penicillium nordicum and Aspergillus ochraceus . No sensorial differences was present among speck produced with or without yeasts added.